KETERKAITAN POLA ASUH DENGAN KNOWLEDGE DAN ATTITUDE TENTANG KEHAMILAN REMAJA PADA SISWA SMA NEGERI 1 GONDANGKABUPATEN MOJOKERTO - Meilinawati SB, Elies; Lukita Dewi, Catur (JURNAL KEPERAWATAN SEHAT, 2014)
Adolescence is an important growth period, adolescence can be the best and can be the worst. The ideal age for pregnancy is 20-30 years old, more or less than that age is a high risk. Today, the teen pregnancy rate in Indonesia is still very high. Adolescent positioned into risk groups because lack of knowledge and rights of adolescents on reproductive health,. Parents tend to avoid discussing sexual matters with children because of ignorance or because of his still taboo talk about sex. The purpose of this study was to analyze the correlation between parenting with the knowledge and attitude of students of SMAN 1 Gondang Mojokerto about teenage pregnancy. This study used a cross sectional research design. Data were collected by using a questionnaire to 179 respondents. The results of of this research is that there is a correlation between parenting with knowledge (p <0.05), and there is a correlation between parenting with attitude of students of SMA Negeri 1 Gondang about teen pregnancy (p <0.05).It is expected that the results of this study can provide a positive contribution to the development of science including: (1) Material considerations in setting health policy and health promotion as a reference in promotive, preventive in improving health status (2) Additional information parenting teens in an effort to keep from falling in understanding and improper sexual behavior.Keyword : parenting, knowledge, attitude, teenage pregnancy